Model of Solving the Motorcycle Racing Problems on the Road of Naughty Teens in Responsibility Area of Provincial Police Region 3 - Naraklam, Pratheep (Journal for Developing the Social and Community, 2019)
This research aimed (1) to study the elements and indicators of solving the motorcycle racing problems on the road of naughty teens, (2) to building the model of solving the motorcycle racing problems on the road of naughty teens, and (3) to confirm the model of solving the motorcycle racing problems on the road of naughty teens. The sample was 400 stakeholders in the responsibility area of Provincial Police Region 3; selected by probability sampling. The instruments were questionnaire, interview and focus group discussion. The data was analyzed by descriptive statistics, multiple regression analysis and content analysis. The research results were found that; The elements and indicators of solving the motorcycle racing problems on the road of naughty teens were 3 elements; (1) Knowledge and understanding in solving the motorcycle racing problems on the road of naughty teens, (2) attitude towards solving the motorcycle racing problems on the road of naughty teens, and behavior of solving the motorcycle racing problems on the road of naughty teens. The hypothesis was tested by stepwise method. (3) The model of solving the motorcycle racing problems by focus group discussion found that model of solving the motorcycle racing problems on the road of naughty teens in the responsibility area of Provincial Police Region 3 could be able for implementation appropriately.